The Global Agenda : Issues and Perspectives - KEGLEY, Charles W. (Random Hause, 1984)
This text offers a balanced set of readings, analyzing the dynamics of world politics with readings written by political scientists. Many of these readings - 43 in all - have been written exclusively for this volume. The book aims to cover the most important and current issues in the study of international relations. The readings are categorized into one of two types: high politics, focusing on peace and security, and low politics, focusing on issues of material and non-material well-being.